PENGARUH DIMENSI STRUKTUR KEPEMILIKAN TERHADAP KINERJA PERUSAHAAN MANUFAKTUR - Lestari, Nopi Puji; Juliarto, Agung (Diponegoro Journal of Accounting, 2017)
This study is conducted to analyze the impact of ownership structure on corporate performance of manufacturing companies. Dimensions of ownership structure are represented by concentrated ownership, managerial ownership and institutional ownership. This research refers to research conducted by Khamis (2015). The population of this study are all manufacturing companies listed on the Indonesian Stock Exchange (IDX) for the periode 2013-2015 . Total Observation of 210  was determined by purposive sampling method. Both an accounting based measure (ROA) and a market based measure (Tobin’s Q) are used to measure corporate performance.There are several control variables were included in this study i.e. age, size, leverage,board size, growth and liquidity ratio. This study uses Ordinary Least Square (OLS) for hypotheses testing.The results show that Ownership concentration have a negative effect with statistical significance on corporate performance. Managerial ownership was found to have a positive effect with statistical significance on corporate performance. Institutional ownership was not to have a significance effect on corporate performance ,however it found that institutional ownership has a positive effect on corporate performance. The implication of this study showed that manajerial ownership and institutional ownership can reduce conflict of interest and increase corporate performance.However, concentrated ownership which creates majority and minority shareholders creating a potential conflict that may effect the company performance.